Вплив левотироксину на стан ендотеліальної дисфункції у пацієнтів з поєднаним перебігом артеріальної гіпертензії, цукрового діабету 2 типу та субклінічного гіпотиреозу - Немцова, Валерія Даниілівна (Чорноморський національний університет ім. Петра Могили, 2020)
Мета – оцінити вплив додаткового призначення левотироксина на стан ендотелія судин та маркери хронічного системного запалення у пацієнтів з поєднаним перебігом артеріальної гіпертензії, цукрового діабету 2 типа та субклінічного гіпотиреозу. Включено 32 пацієнта (середній вік 59,3±3,5 років) з артеріальною гіпертензією II стадії в поєднанні з цукровим діабетом 2 типу та субклінічним гіпотиреозом. Критерій включення – рівень тиреотропного гормону більш 6,0 мкМОд/мл при скрінінговому дослідженні. Левотироксин був призначений в індивідуально підібраних дозах від 12,5 до 50 мкг/добу з поступовим титруванням дози до досягнення еутиреозу. Термін спостереження – 1 рік. Визначення рівня васкулоендотеліального фактору росту (VEGF–A), С–реактивного протеїну, фактору некрозу пухлин–α (ФНП–α) в плазмі крові проводили імуноферментним методом, кількість десквамуючих циркулюючих ендотеліальних клітин в крові – за методом Hladovec J. в модифікації Rajec J. і співавт. методом фазово–контрастної мікроскопії. Статистичну обробку даних проводили за допомогою комп'ютерної програми SPSS 21.0. У пацієнтів з артеріальною гіпертензією, цукровим діабетом 2 типу та субклінічним гіпотиреозом на фоні зниженої функції щитоподібної залози були виявлені ознаки хронічного системного запалення та дисфункції ендотелія. Кореляційний аналіз виявив наявність позитивного зв'язку між рівнями VEGF–А та тиреотропного гормону (r=0,421, р=0,001). Лікування левотироксином супроводжу-валося поліпшенням функціонального стану щитоподібної залози, достовірним зниженням рівня VE-GF–А (до лікування 585,67±35,08 пг/мл, після лікування – 462,58±32,18 пг/мл, р<0,001 відповідно), але не було відзначено істотного зниження рівня десквамуючих циркулюючих ендотеліальних клітин (до лікування – 10,28±0,61 (кл./100 мкл), після лікування – 10,16±0,59 (кл. /100 мкл), р=0,083 відповідно), достовірним зниженням рівня С–реактивного протеїну (р<0,001) та ФНП - α(р<0,001). Кореляційний аналіз після лікування виявив наявність позитивного зв'язку між рівнями вільного Т3 та VEGF–А(r=0,481, р=0,015), і негативного зв'язку між кількістю десквамуючих циркулюючих ендотеліальних клітин та рівнем вільного Т4 (r= –0,457, р=0,022). Застосування левотироксину в комплексному лікуванні хворих з поєднаним перебігом артеріальної гіпертензії, цукрового діабету 2 типа та субклінічним гіпотиреозом супроводжується поліпшенням функціонального стану ендотелія, що в сукупності зі зниженням рівнів маркерів хронічного системного запалення може розцінюватися як позитивний вплив на кардіо–васкулярний ризик, що покращує прогноз у цієї когорти хворих.

Abstract. The purpose of the study was to evaluate the effect of levothyroxine supplementation on vascular endothelium status and markers of chronic systemic inflammation in patients with combined course of arterial hypertension, type 2 diabetes mellitus, and subclinical hypothyroidism. Material and methods.The study included 32 patients (mean age 59.3±3.5 years) with arterial hypertension stage II in combination with type 2 diabetes mellitus and subclinical hypothyroidism. The inclusion criterion was the presence of a TSH level of more than 6.0 mIU / L in the screening period. The control group consisted of 30 representatives by age and gender, without cardiovascular disease and endocrinopathies. Levothyroxine was administered in individually selected doses of 12.5 to 50 mg/day with gradual dose titration (21 day titration step) until euthyroidism was reached. The period of observation was 1 year, 28 (87.5 %) patients completed the study. Plasma levels of vasculoendothelial growth factor (VEGF–A), C–reactive protein, tumor necrosis factor–α (TNF–α) were checked by ELISA. The number of desquamating circulating endothelial cells in the blood was determined by the method of Hladovec J. in the modification of Rajec J. et al. using phase contrast microscopy. Statistical processing of data was performed with the computer program SPSS 21.0. Results and discussion.A comparative analysis revealed signs of chronic systemic inflammation, endothe-lial dysfunction on the background of decreased thyroid function in patients with arterial hypertension, type 2 diabetes mellitus and subclinical hypothyroidism comparedwith the control group. Correlation analysis revealed a positive correlation between VEGF–A and TSH levels (r=0.421, p=0.001). Improvement of the thyroid function on the background of treatment with levothyroxine was accompanied by a significant decrease in the level of VEGF–A (before treatment 585,67±35,08 pg / ml, after treatment – 462,58±32,18 pg / ml, p<0,001, respec-tively), not a significant decrease in the desquamating circulating endothelial cells count (before treatment it was 10.28±0.61 (cell./100 μl), after treatment it was 10.16±0.59 (cell./100 μl), p = 0.083, respectively), a slight but significant decrease of C–reactive protein (p<0.001) and TNF–α(p <0.001). Post–treatment correlation analysis revealed a positive relationship between free T3 and VEGF–A levels (r = 0.481, p = 0.015), and a negative rela-tionship between desquamating circulating endothelial cells and free T4 levels (r = 0.457, p = 0.022). Conclusion. The use of levothyroxine in the complex treatmentof patients with combined course of arterial hypertension, type 2 diabetes mellitus and subclinicalhypothyroidism was accompanied by an improvement in the functional state of the endothelium,which together with decreased markers of chronic systemic inflammation improved the prognosis for this cohort of patients.
The effect of levothyroxine on the state of endothelial dysfunction in patients with a combined course of arterial hypertension, type 2 diabetes mellitus and subclinical hypothyroidism
Keywords: артеріальна гіпертензія; цукровий діабет 2 типа; субклінічний гіпотиреоз; ендотеліальна дисфункція; левотироксин; arterial hypertension; type 2 diabetes mellitus; subclinical hypothyroidism; endothelial dysfunction; levothyroxine